Differences in Fasting Total Cholesterol Levels in Serum and Plasma Edta Samples Using Biosystem Ba200 (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Examination of total cholesterol levels in serum samples is more often used as an examination material, but serum samples often encounter difficulties due to insufficient blood volume or the condition of the serum being lysed due to poor sampling. Many studies have been conducted to look at total cholesterol levels using the anticoagulants EDTA, Sodium Citrate, and Sodium Oxalate to look at differences in total cholesterol levels, but not many studies have looked at tests of differences in total cholesterol test results during fasting with serum and EDTA. This study aims to determine differences in total cholesterol levels in the fasting state of EDTA serum and plasma samples using the BA200 biosystem. The type of research used was cross sectional, which was carried out at the Hematology Laboratory of the Palembang Muhammadiyah Institute of Health Sciences and Technology and the Palembang Health Laboratory Center. A sample of 30 people was taken purposively, female, and fasting for 10 hours. Based on the results of examining total cholesterol levels in a fasting state using the Biosystem BA200, the average result for serum samples was 4.8 mmol/L and the average for plasma samples was 4.7 mmol/L. Analysis was carried out using an independent sample T-test and the result was p = 0.00, the hypothesis was accepted. This research can conclude that there is a difference between the results of examining total cholesterol levels in fasting serum and EDTA plasma samples using the BA200 biosystem.